Political Sensitivity and Carbon Emissions: Evidence From a Quasi-Natural Experiment of Leadership Change in China - Su, Zhi; Liu, Peng; Wu, Liyan (Frontiers in Energy Research, 2022)
While there is extensive literature assessing the impact of command-and-control and market-incentive environmental regulation on carbon emissions, it overlooks the fact that command-and-control environmental regulation and market-incentive environmental regulation are the embodiment of the national concept of green development. When a national leader with a green development philosophy is in power, local governments (due to the competition among them) adjust the economic development strategies and targets in their jurisdictions according to the leaders’ philosophy, resulting in differences in urban carbon emissions. Based on Chinese urban panel data from 2010 to 2016, this study uses a difference-in-differences approach to assess the impact of a national leader with a green development philosophy in power on carbon emissions in cities with different political sensitivities and the mechanisms of the impact. Our study finds that after the change in national leadership, the carbon intensity of high politically sensitive cities decreases significantly compared to low politically sensitive cities. We further find that increasing urban green areas and limiting the development of high-polluting industries are two ways to reduce carbon emission intensity in highly politically sensitive cities. A heterogeneity test demonstrates that the higher the level of economic development of the region where the city is located, the fewer the number of industrial enterprises in the city, the lower the total industrial output value of the city, and the more domestic enterprises in the city, proving that the change of national leaders more significantly impacts the city’s carbon emission. Our study suggests that policymakers should pay careful attention to the system of appraisal of officials, urban greening and development of highly polluting industries, and differentiated environmental policies.